Inter-market Variability of Smallholder Beef Cattle Farming in East Java Indonesia - Andrie Kisroh Sunyigono; Isdiana Suprapti; Nurul Arifiyanti (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
Indonesia has failed to achieve meat self-sufficiency; meanwhile, East Java is among the centers of beef cattle with a relatively high contribution in terms of GDP and employment. Therefore, this study aims to identify and analyze the market structure of the beef cattle commodity chain by considering the concentration ratio, Gini Index, as well as barriers to exit and entry. The study was conducted in Malang Regency and Sapudi Island, with 164 respondents, which consisted of calf suppliers, farmers, traders, and slaughterhouses. Furthermore, the analytical tools used include descriptive, concentration ratio, Gini Coefficient, and analysis of barriers to entry and exit. Based on the results, the market structures in the beef cattle commodity chain in terms of its input market was perfect competition, while the intermediate and output market was oligopoly. These results were confirmed by the concentration ratios of calf suppliers and farmers, which were lower than the ratios of traders and slaughterhouses. Although the market structures were different, their Gini Coefficients are almost similar because a value of 0.2 showed an equitable distribution. Additionally, the barriers to entry into the market were high investment with a large number of import and market problems. Meanwhile, the barriers to exit the market were a large number of potential demands, high investment, and a source of income.